How to Monitor an Ambitious Agenda : The Africa Results Monitoring System - Mohan, P. C. (World Bank, Washington, DC, 2012)
The Africa Results Monitoring System (AfricaRMS) is a new tool for dynamic learning that monitors and reports data and stories of African development. It is meant to bolster the Africa Region's Results Agenda. AfricaRMS is a first-of-its kind system in the Bank, and the only website where anyone can see how the Bank spends, where and what is obtained from the spending, and where results are achieved. It offers a clear window into Bank work and a comprehensive view of country growth in Africa. This brief tells the story of AfricaRMS, how it's applied, its structure, about the team that built it, and partner's countries.